Development of self-consolidating rubberized concrete incorporating silica fume. (10th February 2018) - AbdelAleem, Basem H.; Hassan, Assem A.A.
Highlights: SLFSCRC mixtures with different CR and binder content were investigated. Increasing CR content negatively affected the mechanical properties of mixtures. Performance of SLF compared to other SCMs was investigated. Adding MK and SFs to SLFSCRC mixtures improved mechanical properties of mixtures. Mixtures with maximized percentage of CR and SFs further enhanced the STS and FS. Abstract: This investigation was carried out to evaluate the effect of using silica fume on the development and optimization of self-consolidating rubberized concrete (SCRC). In particular, the investigation aimed to optimize successful silica fume self-consolidating rubberized concrete (SLFSCRC) mixtures with maximized percentage of crumb rubber (CR) (as a partial replacement of fine aggregate) and minimized strength reduction. The study also compared the behaviour of silica fume (SLF) with other supplementary cementitious materials (SCMs) in optimized SCRC mixtures. The results indicated that the use of SLF helped to develop SCRC mixtures with improved strength and acceptable fresh properties with up to 25% CR. Using SLF or metakaolin (MK) in SCRC exhibited superior behaviour among other SCMs in terms of strength. However, using SLF in SCRC showed better mixture flowability and less dosage of high range of water reducer admixture compared to using MK in SCRC. It was also noticed that adding steel fibres (SFs) to SLFSCRC mixtures greatly enhanced the mechanical properties, especially the splitting tensile strength and flexural strength. The results also showed that since there is no challenge to achieving acceptable self-compactibility (especially passing ability) in vibrated rubberized concrete, it was possible to develop silica fume vibrated rubberized concrete (SLFVRC) with higher percentages of CR and SFs and with further improved flexural and tensile strengths.